Biodiversity and species richness of oribatid mites (Acari: Oribatida) in orchards of East Azerbaijan province, Iran - Maryam Rahgozar; Karim Haddad Irani–Nejad; Mohammad–Reza Zargaran; Alirezai Saboori (Persian Journal of Acarology)
Oribatid mites are one of the dominant soil microarthropods. These mites have an important role in increasing soil fertility through organic materials decomposition. Oribatid mite communities (Acari: Oribatida) were investigated in orchards of five regions (Ahar, Kaleibar, Varzaghan, Heris and Horand) in East Azerbaijan province, Iran. The oribatid mites were studied in each orchard (apple orchards with size of approximately 0.4 ha were selected) by collecting 12 samples taken from a maximum depth of 20 cm. Sampling was performed for six months in 2015. The oribatid species diversity (Shannon-Wiener index), Species richness (Rarefaction and Jackknife methods), Evenness by Shannon's index and similarity (Sorensen index) were calculated with Ecological Methodology 6.0 software for all the regions. A total of 75 species belonging to 57 genera and 38 families of oribatid mites were collected and identified. The highest number of species (54 spp.) was found in the orchards of Kaleibar, while the studied orchards of Varzaghan had the lowest number of species (21 spp.). One–way ANOVA analysis showed that the Shannon–Wiener species diversity was highest in Kaleibar (H = 3.409) and Ahar (H = 3.419). Also, Kaleibar and Ahar had the highest species richness (Kaleibar: 79.8 species, Ahar: 70.7 species). Among studied regions, Kaleibar and Ahar had the highest species richness and species diversity but Varzaghan showed the lowest values, apparently because of geographical and climate differences between these regions.